PELATIHAN DIVERSIFIKASI OLAHAN BAWANG MERAH MENJADI BAWANG GORENG VARIAN RASA UNTUK MENINGKATKAN PRODUKTIVITAS IBU RUMAH TANGGA DI DESA DONGGOBOLO KABUPATEN BIMA - Kusumayadi, Firmansyah; Aprianti, Kartin; Yusuf, Muhammad; Muhajirin; Ismunandar (Transpublika Publisher, 2022)
The purpose of this community service activity is to provide training related to the manufacture of various flavored fried onions for the community, especially housewives in Donggobolo Village, Woha District, Bima Regency and to find out the response of housewives in Donggobolo Village to training in making packaged fried onions. The method of this community service activity uses the lecture method, demonstration, question and answer method and exercises in the manufacture and processing of fried onions. This training involved members of the Real Work Lecture students who were accompanied by assistant lecturers from the Management Study Program and housewives in Donggobolo Village. There are results from training on making fried onions of various flavors conducted by housewives in Donggobolo Village, namely (1) the results of the evaluation of processed fried onions made by training participants are generally in the good category with an average success of 75%, (2) The response from housewives to the implementation of the training on making fried onions was very enthusiastic, seen from the attendance reaching 90% and participating in the activity from beginning to end.